THE EXPERIENCE OF REMICADE USAGE IN THE TREATMENT OF RHEUMATOID ARTHRITIS PTS - N F Soroka; I. P. Grigorchuk; I N Alikevich (Научно-практическая ревматология)
A bstract. Objective. To study the efficacy and tolerability of Remicade in RA Material and methods. 20 reliable RA pts compatible to criteria for inclusion into the study and without exclusion criteria. 18 women and 2 men aged 30-60 and older wilh disease term from 3 lo 10 years and longer. In 14 pts RA activity was of 2" J and in 6 pts оГ 3d degree. All pts long period to the beginning of the study had methotrexate in dosage of 7.5-10 mg/week and NSAID, 4 pts had metipred 4-8 mg/day. Remicade was administrated i.v. in droplet in dosage 3 ml/kg of body weight per 250.0 ml of physiological solution lor 2 hours in 0.2, 6, 8 weeks (total 9 infusions for 54 weeks). Results. Full course of Remicade therapy on the background of methotrexate was carried out in 19 pts. All pts demonstrated speedy (after I м infusion) positive effect as reliable decrease of the number of inflamed joints, period of morning stiffness and ESR. Results of 54-weck course assessed as «excellent» in 9, «good» in 8 and «satisfactory» in 2 pts. In 6 cases remission was observed. Remicade tolerabilily was satisfactory. Only in 1 pts during the 7"' infusion bronchospasm and attack Quincke’s oedema she was excluded from further study. Transient hypotension was noticed in 2 pts. In 3 cases infection exacerbation developed (otitis, pneumonia) which required antibiotics use.